2017
DOI: 10.1007/s40069-017-0208-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Compatibility of Repair Materials for Concrete Structures

Abstract: This study evaluates the compatibility of repair materials for concrete bridge decks. A new compatibility test set-up was designed and tested based on the concrete bridge deck cracking and delamination mechanism theory. The repair materials used in this study include lab formulated inorganic nano-aluminum silicates and commercially available organic two-part epoxy systems. Two different lab test-setups are proposed in this study: a prototype and a full-scale test. The developed test procedures were effective i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The concrete with limited slag content can increase the bond strength with higher compressive strength. Venkiteela et al (2017) have evaluated the concrete repair materials compatibility for bridge decks. Moreover, a new set-up for compatibility was also developed and tested depending on the delamination theory and cracking in bridge decks.…”
Section: High Oscillatory Properties Has Been Recordedmentioning
confidence: 99%
“…The concrete with limited slag content can increase the bond strength with higher compressive strength. Venkiteela et al (2017) have evaluated the concrete repair materials compatibility for bridge decks. Moreover, a new set-up for compatibility was also developed and tested depending on the delamination theory and cracking in bridge decks.…”
Section: High Oscillatory Properties Has Been Recordedmentioning
confidence: 99%
“…The results showed that the coarse aggregate used in this study complies with the standard (IQS No. 45/1984) limits Size (5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Gravel must be washed to remove clay and salts and then stored in containers in a Saturated Surface Dry (SSD) condition before use it.…”
Section: Coarse Aggregatementioning
confidence: 99%
“…It is critical to study compatibility of repair materials at the same time with bond strength to well comprehend the performance of repair materials. There are no conventional techniques to determine whether repair materials are compatible with concrete substrates [8].…”
Section: Introductionmentioning
confidence: 99%
“…The use of epoxy polymer solutions is widespread in the construction industry. Currently, repair solutions [1,2], compositions for protection of concrete surfaces from ag-gressive effects [3,4], protection of steel reinforcement in concrete [5], etc. require these materials.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%